Impact of luminal and systemic endotoxin exposure on gut function, immune response and performance of chickens. Issue 2 (1st June 2016) - Ghareeb, K.; Awad, W.A.; Böhm, J.; Zebeli, Q.
Abstract : The gastrointestinal tract is a large reservoir of both Gram positive and negative bacteria, of which the Gram negative bacteria act as a source of lipopolysaccharide (LPS). Luminal LPS, commonly known as endotoxin, can enter systemic circulation via paracellular and transcellular permeation. It has been shown that endotoxin exposure can increase intestinal paracellular permeability and alter intestinal structure and function, resulting in impaired absorption and utilisation of nutrients with negative impact on both poultry heath and growth. Acute exposure to large amounts of endotoxin suppresses feed intake in chickens and activation of the innate immune system. Substantial evidence suggests that endotoxin is recognised via toll-like receptor (TLR)-4, located on the surface of immune cells, which activates kinases to enhance the transcription of pro-inflammatory cytokines such as tumour necrosis factor alpha (TNF-α) and interleukin (IL)-1 and 6 which mediate the inhibitory effect of endotoxin on the intestinal nutrient absorption. Inflammation can divert energy and nutrients away from growth supp and into supporting the immune system responses, leading to growth suppression and lowered feed efficiency. In addition, sustained exposure to endotoxin may elicit tolerance, which can make animals refractory against secondary Gram-negative infections. In this review, the effects of endotoxin on intestinal barrier functions and the subsequent negative impacts on the production of chickens are summarised. Overall, this review combines the current knowledge of the chicken's intestinal responses to Gram negative bacterial infection, illustrating the importance of gut health in defence against bacterial infections and improving poultry health, growth and welfare.